2018
DOI: 10.1038/s41598-018-23779-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CaMKIIα and β splice-variant distribution among brain regions reveals isoform-specific differences in holoenzyme formation

Abstract: Four CaMKII isoforms are encoded by distinct genes, and alternative splicing within the variable linker-region generates additional diversity. The α and β isoforms are largely brain-specific, where they mediate synaptic functions underlying learning, memory and cognition. Here, we determined the α and β splice-variant distribution among different mouse brain regions. Surprisingly, the nuclear variant αB was detected in all regions, and even dominated in hypothalamus and brain stem. For CaMKIIβ, the full-length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 62 publications
(100 reference statements)
4
75
0
Order By: Relevance
“…This splice variant plays an important role in membrane anchoring using its hydrophobic N-terminal domain (28). Finally, it was shown that alternative splicing within the hub might regulate oligomerization (5). Roles for the remaining exons have yet to be delineated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This splice variant plays an important role in membrane anchoring using its hydrophobic N-terminal domain (28). Finally, it was shown that alternative splicing within the hub might regulate oligomerization (5). Roles for the remaining exons have yet to be delineated.…”
Section: Introductionmentioning
confidence: 99%
“…CaMKII is expressed throughout the human body, which facilitates its role in these disparate functions. There are four human genes that encode CaMKII: CaMKIIα and β (predominantly in brain), CaMKIIδ (predominant in heart) and CaMKIIγ (multiple organ systems, including egg and sperm) (5)(6)(7). In all four genes, each CaMKII subunit is comprised of a kinase domain, regulatory segment, variable linker region, and a hub domain (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that the variable region, where CaMKIIα and β differ most, is subject to alternative splicing in all CaMKII isoforms. Regarding CaMKIIβ, four splicing variants, β, β’, βe, and β’e, were discovered in the brain, but only β and β’variants contain a FABD and are, therefore, able to bind to F-actin [ 10 , 11 , 12 , 13 ] ( Figure 1 A).…”
Section: Features Of Camkiiβmentioning
confidence: 99%
“…In the mature brain, the full-length variant CaMKIIβ predominate in most brain regions, except in the hypothalamus and brainstem where equal β and β’ are detected [ 11 ]. In the whole embryonic brain, βe predominate at E16 and E18 [ 11 ]. However, in the embryonic cerebral cortex, β and β’ proteins are dominant at E16.5 [ 18 ].…”
Section: Features Of Camkiiβmentioning
confidence: 99%
“…Their most important difference is the length of the linker, which affects the frequency response of CaMKII to Ca 2+ /CaM pulses [12]. In this work, we study the predominant form of CaMKII found in the brain[13, 14], the α isoform, with a β 7 linker connecting the C and N terminals. This linker has been shown to have a reduced kinase activity [15].…”
Section: Introductionmentioning
confidence: 99%